Anti-inflammatory effect of ozonated krill (Euphausia superba) oil in lipopolysaccharide-stimulated RAW 264.7 macrophages - Hong-Deok Kim; Soo-Bin Lee; Seok-Chun Ko; Won-Kyo Jung; Young-Mog Kim; Seon-Bong Kim (Fisheries and Aquatic Sciences, 2018)
Abstract Background Inflammation has been known to associate with many human diseases. The objective of this study was to evaluate an anti-inflammatory effect of ozonated krill (Euphausia superba) oil, which was prepared by the treatment of krill oil using ozone gas. The anti-inflammatory activity was evaluated in lipopolysaccharide (LPS)-stimulated RAW 264.7 macrophages. Results Ozonated krill oil significantly inhibited nitric oxide (NO) production and suppressed the mRNA and protein expression of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) in LPS-stimulated RAW 264.7 macrophages. Ozonated krill oil also reduced the mRNA expression of inflammatory cytokines such as interleukin (IL)-1β, IL-6, and tumor necrosis factor (TNF)-α in LPS-stimulated RAW 264.7 macrophages. To elucidate the mechanism underlying the anti-inflammatory activity of ozonated krill oil, we evaluated the effects of ozonated krill oil on the activation of mitogen-activated protein kinases (MAPKs) pathway. Ozonated krill oil suppressed the LPS-stimulated phosphorylation of p38 MAPK and c-Jun N-terminal kinases (JNK). Conclusion This study revealed that the ozonated krill oil exhibited an anti-inflammatory effect in LPS-stimulated RAW 264.7 macrophages. To the best of our knowledge, this is the first report that ozonated krill oil suppressed pro-inflammatory mediator and cytokine expression in LPS-stimulated RAW 264.7 macrophages by inhibiting the phosphorylation of p38 MAPK and JNK.